2014
DOI: 10.3344/kjp.2014.27.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salivary Cortisol and Anxiety Levels in Myofascial Pain Dysfunction Syndrome

Abstract: BackgroundMyofascial pain dysfunction syndrome (MPDS), otherwise called myofascial pain is one of the most common temporomandibular disorders, which in turn is the most common cause of orofacial pain of non-dental origin. Its etiology is multifactorial and still poorly understood. Psychological factors have been shown to play a role in the etiology. The aim of the study was to evaluate the association between anxiety and salivary cortisol levels in patients with myofascial pain.MethodsTwenty patients suffering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 17 publications
2
17
0
5
Order By: Relevance
“…Eleven of these, performed on a population of 5802 subjects, showed this relationship to be significantly correlated (Mongini et al, 2007; Nifosì et al, 2007; Komiyama et al, 2008; de Tommaso et al, 2009; Galli et al, 2009; Manfredini et al, 2011; Guarda-Nardini et al, 2012; Kindler et al, 2012; Klasser et al, 2014; Nadendla et al, 2014). The quality of evidence for this group was moderate.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven of these, performed on a population of 5802 subjects, showed this relationship to be significantly correlated (Mongini et al, 2007; Nifosì et al, 2007; Komiyama et al, 2008; de Tommaso et al, 2009; Galli et al, 2009; Manfredini et al, 2011; Guarda-Nardini et al, 2012; Kindler et al, 2012; Klasser et al, 2014; Nadendla et al, 2014). The quality of evidence for this group was moderate.…”
Section: Resultsmentioning
confidence: 99%
“…Many painful syndromes including myofascial pain syndrome, fibromyalgia, and sympathetic maintained pain syndromes, are commonly combined with anxiety [ 34 , 35 ]. Etifoxine shows less adverse effects of anterograde amnesia, sedation, impaired psychomotor performance, and withdrawal syndromes than those of benzodiazepines.…”
Section: Discussionmentioning
confidence: 99%
“…As the literature has suggested that the links between acute and chronic stress, psychopathology, and HPA function may differ among males and females ( 24 - 31 ), in the current study we examined sex differences in the predictive role of anxiety symptoms during adolescence on annual decline of morning salivary cortisol level during early adulthood among Blacks. As most of the research on the association between HPA axis and anxiety originates from cross-sectional studies ( 1 , 19 ), the current longitudinal study with long term follow up is believed to make a unique contribution to the literature.…”
Section: Objectivesmentioning
confidence: 99%